1993
DOI: 10.3382/ps.0720193
|View full text |Cite
|
Sign up to set email alerts
|

Precocious Semen Production in Turkeys

Abstract: Turkey toms were reared under short days [either 8 h light (L): 16 h dark (D) or 12L:12D] and photostimulated by transfer to 14L:10D between 7 and 22 wk of age. Photostimulation between 12 and 15 wk of age initiates semen production at 18 to 20 wk of age. The fertilizing capacity of semen produced by these males is normal and the output of spermatozoa is unaffected when semen production is initiated precociously. Daylengths of 8L:16D or 12L:12D during the rearing period had no influence on subsequent reproduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Similar observations were reported for guineafowl [20] and fowl [21] exposed to strict short days. We suggest that this cannot be attributed to juvenile photorefractoriness that is expressed in wild birds not having reached full body development [19]. Our study also confirmed previous observations that a short, reputedly non-stimulatory photoperiod may induce precocious sexual maturity (26-29 wk) in a minority (here about 30%) of the experimental population [9].…”
Section: Discussionsupporting
confidence: 80%
“…Similar observations were reported for guineafowl [20] and fowl [21] exposed to strict short days. We suggest that this cannot be attributed to juvenile photorefractoriness that is expressed in wild birds not having reached full body development [19]. Our study also confirmed previous observations that a short, reputedly non-stimulatory photoperiod may induce precocious sexual maturity (26-29 wk) in a minority (here about 30%) of the experimental population [9].…”
Section: Discussionsupporting
confidence: 80%
“…This earlier onset of puberty was associated with higher levels of LH after 18 wk of age. Semen production at an early age was also observed in male turkeys in the study of Etches et al [26], but no correlated hormone data were presented by these authors. There are reports that FSH in male chickens increases during development [23,24]; this might induce sexual maturation and semen production.…”
Section: Discussionmentioning
confidence: 60%